Management of Corneal Astigmatism by Limbal Relaxing Incisions during Phacoemulsification (Central Medical College Journal, 2024)
Background: Phacoemulsification is one of the most successfully and commonly performed cataract surgeries worldwide. Modern cataract and refractive surgery aims not only to improve vision but to provide a good unaided visual acuity. Correcting astigmatic errors and control of surgically induced astigmatism are now an integral part of such operative procedures. Objective: To analyze the effectiveness and safety of limbal relaxing incisions (LRI) in correcting keratometric astigmatism during phacoemulsification. Method: A prospective study of two groups: control group and treatment group. Treatment group included 50 eyes of 50 patients who had combined clear corneal phacoemulsification, IOL implantation and LRI. Control group included 50 eyes of 50 patients who had clear corneal phacoemulsification and IOL implantation. Postoperative keratometric astigmatism was measured at 1 week, 1 month, 3 months and 6 months. Result: LRI significantly decreased keratometric astigmatism in patients with preexisting astigmatism compared with astigmatic changes in the control group. In eyes with LRI, the mean keratometric astigmatism was 0.31±0.17 D (range 0 to 0.5 D) at 1 week, 0.39± 0.21 D (range 0 to 0.85 D) at 1 month, respectively reduced by 2.43 D and 2.29 D at 1 week and 1 month postoperatively (P=0.000, P=0.000), and postoperative astigmatism was stable until 6 months follow-up. The keratometric astigmatism of all patients decreased to less than 1.00 D postoperatively. Conclusion: LRI was a practical, simple, safe and effective method to reduce preexisting astigmatism during phacoemulsification.Central Medical College Journal Vol 7 No 2 July 2023 Page: 82-86